Beyond sacred violence : a comparative study of sacrifice - McClymond, Kathryn, 1960- (Book collections on Project MUSE., 2008)
For many Westerners, the term sacrifice is associated with ancient, often primitive ritual practices. It suggests the death--frequently violent, often bloody--of an animal victim, usually with the aim of atoning for human guilt. Sacrifice is a serious ritual, culminating in a dramatic event. The reality of religious sacrificial acts across the globe and throughout history is, however, more expansive and inclusive. In Beyond Sacred Violence, Kathryn McClymond argues that the modern Western world's reductive understanding of sacrifice simplifies an enormously broad and dynamic cluster of religious activities. Drawing on a comparative study of Vedic and Jewish sacrificial practices, she demonstrates not only that sacrifice has no single, essential, identifying characteristic but also that the elements most frequently attributed to such acts--death and violence--are not universal. McClymond reveals that the world of religious sacrifice varies greatly, including grain-based offerings, precious liquids, and complex interdependent activities. --